EFFECT OF Artemisia vulgaris LEAF EXTRACT ON ANTIOXIDANT STATUS OF PRIMARY CHICK EMBRYO FIBROBLASTS - SHARMILA, K.,; PADMA, P.R., (International Journal of Pharma and Bio Sciences, 2014)
An imbalance between the pro-oxidants and/or free radicals on one side and antioxidants on the other results in oxidative stress that has shown to play a role in the etiology and pathophysiology of various human diseases. Antioxidant defense systems, both enzymic and non-enzymic scavenge the free radicals formed continuously in the body. Natural products of plant origin are gaining much importance in recent years for their pharmacological properties including antioxidant and antitumor activity. The present study focuses on the use of the methanolic extract of Artemisia vulgaris leaf extract on the enzymic and non-enzymic antioxidant status of chick embryo fibroblasts subjected to oxidative stress. The leaf extract of Artemisia vulgaris possess certain active ingredients that improve the antioxidant status in primary cells subjected to oxidative stress. Therefore, this experimental evidence suggests the use of the candidate plant for the treatment of human pathologies in which free radicals play a major role.